A discussion of the paper "Effect of design parameters on microstructure of steel-concrete interface in reinforced concrete". (February 2020) - Zhang, Zhidong; Angst, Ueli
Abstract: The steel-concrete interface is fundamental to many aspects related to the performance of reinforced concrete, particularly for corrosion behavior. A recently published paper by Chen et al. [Effect of design parameters on microstructure of steel-concrete interface in reinforced concrete, Cem. Concr. Res. 119 (2019) 1–10] quantitatively characterized the thickness of the gap observed between the steel and concrete. Considering the low number of available publications, studies documenting the microstructure at the steel-concrete interface are important. However, in our discussion, we think that aspects related to the terminology, the specimen preparation and possible experimental artefacts in the discussed paper can be improved.